Platform capitalism, music production and consumption: the case of Spotify - Masís González, Tadeo (2021)
In the context of recent technological and economic changes mediated by an algorithmic capitalism, the present work studies the change that implies the incursion of platforms in the music industry, as well as their consequences regarding the consumption and production of music. Special attention will be put to the case of Latin America. This analysis includes a review of recent changes in the digital economy through the notion of art worlds. It is evident the emergence of a new actor in the music industry, which assumes roles such as the distribution of musical works and artistic curatorship, thus altering the networks of cooperation and dependence in the music industry. These transformations do not only occur on a global scale, but have potential effects for the Latin American case.